AN EXPERIMENTAL STUDY OF OXYGEN ISOTOPE FRACTIONATION BETWEEN WAIRAKITE AND WATER - Noto M.; Kusakabe M. (My University, 1997)
The analytical technique for determining oxygen isotopic ratios of wairakite has been carefully examined. Channel water in wairakite was separated from its aluminosilicate framework by dehydration in vacuum at various temperatures from 250 to 950°C. Dehydration at temperatures greater than 400°C resulted in erroneous isotopic ratios of the framework oxygen because of oxygen isotopic exchange between the framework oxygen and dehydrating water. The optimum conditions are dehydration of the channel water at 300°C for 24 h, followed by stepwise heating at 350°C for 12 h, 400°C for 5 h, and finally at 700°C for 15 min. With this stepwise heating, isotopic measurements of wairakite framework oxygen can be satisfactorily achieved within an accuracy of +/-0.1%%.The oxygen isotope fractionation factor for the wairakite-water system has been experimentally determined at temperatures between 250 and 400°C and pressures between 0.5 to 1.5 kbar. The equilibrium fractionation factor between framework oxygen and external water is expressed by the following equation: 103 1n αframework oxygen-external water = 2.46 (106/T2) - 1.76 The fractionation factor for the channel water-external water is given by 103 1n αchannel water-external water = 0.79 (106/T2) - 3.07 In the temperature range studied, the framework-water fractionation of wairakite is very similar to that of analcime (Karlsson and Clayton, 1990a) and stilbite (Feng and Savin, 1993b). The negative fractionation for the channel water-external water of wairakite (-3 to 0%%) is consistent with that for analcime and stilbite, but the magnitude is less than that of analcime and stilbite.Almost complete oxygen isotopic exchange during the hydrothermal runs indicates that the exchange between wairakite framework oxygen and water is rapid compared to that of the other silicate-water systems. This implies that the δ18O value of natural wairakite is controlled by retrograde re-equilibration under hydrothermal conditions. The grain size did not change during the hydrothermal runs, suggesting that the exchange mechanism was dominated by sorption-exchange-desorption processes as proposed by Karlsson and Clayton (1990a). However, scanning electron microscopy images of the run products showed that the grain surfaces of the exchanged wairakite were covered by newly deposited crystals, suggesting that dissolution-crystallization was also involved to a small extent.